Unfolded protein response markers Grp78 and eIF2alpha are upregulated with increasing alpha‐synuclein levels in Lewy body disease - Hrabos, D; Poggiolini, I; Civitelli, L; Galli, E; Esapa, C; Saarma, M; Lindholm, P; Parkkinen, L (Wiley, 2024)
Aims: Endoplasmic reticulum stress followed by the unfolded protein response is one of the cellular mechanisms contributing to the progression of α‐synuclein pathology in Parkinson's disease and other Lewy body diseases. We aimed to investigate the activation of endoplasmic reticulum stress and its correlation with α‐synuclein pathology in human post‐mortem brain tissue. Methods: We analysed brain tissue from 45 subjects—14 symptomatic patients with Lewy body disease, 19 subjects with incidental Lewy body disease, and 12 healthy controls. The analysed brain regions included the medulla, pons, midbrain, striatum, amygdala and entorhinal, temporal, frontal and occipital cortex. We analysed activation of endoplasmic reticulum stress via levels of the unfolded protein response‐related proteins (Grp78, eIF2α) and endoplasmic reticulum stress‐regulating neurotrophic factors (MANF, CDNF). Results: We showed that regional levels of two endoplasmic reticulum‐localised neurotrophic factors, MANF and CDNF, did not change in response to accumulating α‐synuclein pathology. The concentration of MANF negatively correlated with age in specific regions. eIF2α was upregulated in the striatum of Lewy body disease patients and correlated with increased α‐synuclein levels. We found the upregulation of chaperone Grp78 in the amygdala and nigral dopaminergic neurons of Lewy body disease patients. Grp78 levels in the amygdala strongly correlated with soluble α‐synuclein levels. Conclusions: Our data suggest a strong but regionally specific change in Grp78 and eIF2α levels, which positively correlates with soluble α‐synuclein levels. Additionally, MANF levels decreased in dopaminergic neurons in the substantia nigra. Our research suggests that endoplasmic reticulum stress activation is not associated with Lewy pathology but rather with soluble α‐synuclein concentration and disease progression.